S15 An observational study of ivacaftor in patients with cystic fibrosis (CF) and selected non-G551D gating mutations: outcomes from the second interim analysis of the VOCAL study. (12th November 2019) - Simmonds, NJ; Castellani, C; Colombo, C; van der Ent, K; Jha, L; DeSouza, C; Thorat, T; Kinnman, N
Abstract : Introduction and objectives: The efficacy and safety of ivacaftor in patients with CF and non- G551D gating mutations were demonstrated in the Phase 3 randomised KONNECTION trial (NCT01614470 ). VOCAL (NCT02445053 ) is an ongoing Phase 4 observational study evaluating real-world effectiveness of ivacaftor in this population (including G178R, S549N/R, G551S, G1244E, S1251N, S1255P, and G1349D mutations). This prespecified second interim analysis describes outcomes over 24 months; 4 years of prospective data collection is planned. Methods: VOCAL includes patients aged ≥6 years with CF from selected sites in the UK, Italy, and the Netherlands. A mixed model for repeated measures of percent predicted FEV1 (ppFEV1 ) and nutritional status was used to analyse on-treatment changes from baseline (start of ivacaftor) in 6-month intervals. A negative binomial model was used to compare 12-month on-treatment rates of pulmonary exacerbations (PEx) with the 12-month rate prior to treatment start. No adjustments for multiple comparisons were performed. Results: By the data cutoff, 68/73 patients (93%) completed 24 months of treatment. Twenty-five (34%) were male. Mean baseline age was 26.9 (SD, 13.5) years. Mean baseline ppFEV1 was 64.82% (SD, 23.61%); least squares (LS) mean (SE; 95% CI) improvement from baseline was 10.78 (1.28; 8.24–13.33) percentage points at 6 months and was sustained through 24 months. In patients aged ≥20 years (n=49), mean baseline body mass index (BMI) was 22.95 kg/m 2 (SD, 3.81); LS mean (SE; 95% CI) change from baseline was 0.81 (0.14; 0.52–1.10) at 6 months and increased to 1.25 (0.21; 0.82–1.68) at 24 months. In patients aged <20 years (n=24), mean baseline BMI z score was -0.41 (SD, 0.90); LS mean (SE; 95% CI) change from baseline was 0.54 (0.11; 0.31–0.77) at 6 months and was sustained through 24 months. Ivacaftor was associated with a >50% reduction in the annual rate of PEx requiring hospitalisations and PEx requiring intravenous antibiotics through 24 months compared with the 12-month pretreatment period. No new safety signals were identified. Conclusions: These real-world data demonstrate the positive impact of ivacaftor treatment on ppFEV1, nutritional parameters, and PEx in patients with non- G551D gating mutations.